An Evaluation Method of Comprehensive Performance of Retrofitted CHP District Heating Systems - Daokun Chong; Haizhu Zhou; Xiaoping Li; Lining Zhou; Yitong Li; Mingda An (Energies, 2023)
There is a big wave in China of retrofitting single-purpose coal-fired systems for district heating into heat-oriented combined heat and power (CHP) systems to save energy. Back-pressure steam turbines (BPSTs) and extraction steam turbines (ESTs) are both common in retrofitted systems, but contrastive analyses of their effects on the systems’ operation performance are lacking. Moreover, comprehensive evaluation methods of the retrofitted systems remain unknown. In this paper, exergy, exergoeconomic, and exergoenvironmental analyses were conducted to evaluate the thermodynamic, economic, and environmental performances of two real CHP systems: system A using a BPST and system B using an EST. Additionally, a new multi-criteria evaluation method based on rank correlation analysis was proposed for the retrofitted system. The results show that system A is better than system B in thermodynamic and environmental aspects but poorer in the economic aspect. Overall, the multi-criteria evaluation result indicates that system A has a better comprehensive performance than system B. Therefore, the BPST has a better effect than the EST on the retrofitted CHP system for district heating in this study. The findings could provide a reference point for retrofitting work in the future.